Respuesta :

10y2 - 17y + 12 = y + 16

10y2 - 17y + 12 - 16 = y

10y2 - 17y - 4 = y

10y2 -17y - y -4 = 0

10y2 -16y - 4 = 0

Now put formula

x = -b +- (square root) b2 - 4ac

                  2a

a = 10 b= -16 c= -4

y = -(-16) +- (square root) -16 - 4 (10) (-4)

                              2(10)

y = 16 +- (square root) -16 - 400

                                 20

y = 16 +- (square root) -416

                          20

y = 16 +- 20.396

               20

Now this +- is the plus minus thingy in which two answers come

The first we will do is +

16 + 20.396                                         16 - 20.396

   20                                                             20

= 1.8198                                                           = -0.2198

ACCESS MORE